2016
DOI: 10.3389/fmolb.2016.00072
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Stem Cell Research- A Ray of Hope in Better Diagnosis and Prognosis in Neurodegenerative Diseases

Abstract: Neurodegeneration and neurodegenerative disorders have been a global health issue affecting the aging population worldwide. Recent advances in stem cell biology have changed the current face of neurodegenerative disease modeling, diagnosis, and transplantation therapeutics. Stem cells also serve the purpose of a simple in-vitro tool for screening therapeutic drugs and chemicals. We present the application of stem cells and induced pluripotent stem cells (iPSCs) in the field of neurodegeneration and address the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…Another COMMD1 binding partner, superoxide dismutase 1, which is regulated by COMMD1 (28,29), has also been shown to regulate normal cellular lifespan (30,31). A G608G mutation in the LMNA gene or the loss of ZMPSTE24 activity resulted in the accumulation of unprocessed prelamin A in cells, which induced DNA damage and genomic instability, and led to premature aging (8,9). DNA damage stimulated the relocalization of COMMD1 into the nucleoplasm and its interaction with alternate reading frame p14ARF (ARF) in humans and p19ARF in mice (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another COMMD1 binding partner, superoxide dismutase 1, which is regulated by COMMD1 (28,29), has also been shown to regulate normal cellular lifespan (30,31). A G608G mutation in the LMNA gene or the loss of ZMPSTE24 activity resulted in the accumulation of unprocessed prelamin A in cells, which induced DNA damage and genomic instability, and led to premature aging (8,9). DNA damage stimulated the relocalization of COMMD1 into the nucleoplasm and its interaction with alternate reading frame p14ARF (ARF) in humans and p19ARF in mice (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have revealed that lamin A serves a structural role during interphase (5), lamin A is increasingly recognized as a mediator, and possibly a regulator, of nuclear processes through its interactions with a variety of nuclear factors, including double-stranded DNA, transcriptional regulators, nuclear membrane-associated proteins and nuclear pore complexes (6,7). Dysfunction of lamin A interrupts chromatin organization, the DNA damage response, telomere maintenance, cellular senescence and apoptosis (8,9). Mutations in the LMNA gene cause a heterogeneous group of human diseases that are collectively termed laminopathies, including progeroid syndromes and premature aging disorders that primarily affect striated muscle, adipose, bone and neuronal tissues, such as Hutchinson-Gilford progeria syndrome (HGPS) (6,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells have the potential to replace damaged cells and thus carry wide applications in regenerative therapeutics and the field of neurodegenerative disorders 14 . Recent studies show that subretinal transplantation of human embryonic stem cell (hESC)-derived RPE could improve, or at least stabilize, visual acuity in patients with dry AMD (n=2) and Stargardt macular dystrophy (n=2).…”
Section: Treatments For Dry Age-related Macular Degenerationmentioning
confidence: 99%
“…Progressive neuronal damage or loss is one of the deterministic features of neurodegenerative diseases such as AD and PD [11,12]. Stem cell-based therapy has exciting potential for neuroprotection [13,14]. The loss of brain function caused by injury and aging can be treated by mobilizing the proliferation and differentiation of endogenous stem cells and replacing them with exogenous stem cells [15,16].…”
Section: Introductionmentioning
confidence: 99%